Residential water and energy nexus for conservation and management: A case study of Tianjin. (21st September 2016) - Jiang, Shan; Wang, Jianhua; Zhao, Yong; Lu, Shibao; Shi, Hongwang; He, Fan
Abstract: As an important part of energy use in the water end-use system, the energy consumption of urban household water use is typical to illustrate the nexus of water and energy. Considering its urban size and population, Tianjin is studied by questionnaires for residential water use and estimated energy intensity. This paper analyzes water-related energy use by studying water end-use data from 504 households and considering family-related impact and technical factors of water appliances. Results show that clothes washing and shower constitute the largest part of water end-use and water-related energy consumption, respectively. Overall simulation assesses the impact of technological improvements, behavioral modification and water-use decrease in household water-related energy use. It indicates that energy saving could reach to 1.69 * 10 10  KWh per year which accounts for 24% of total energy consumption for non-production purposes, which indicate saving water could lead to saving energy. Correlation analysis are used to analyze the relative effects of factors on household water and energy use. The ratio of hand washing and frequency of shower have significant correlation respectively with water end-use and water-related energy consumption, particularly in the parched north. It is suggested to focus on considering the full cost about water resource, strengthening the development of water saving and energy-efficient water appliances, and enhancing the publicity of water saving in the next step. This paper demonstrates the linkage between water and energy in urban water end-use system, thus providing a decision-support tool for water conservation and management.